Testing the asset pricing model of exchange rates with survey data - Anna Naszódi (Magyar Nemzeti Bank, 2011)
This paper proposes a new test for the asset pricing model of the exchange rate. It examines whether the way market analysts generate their forecasts is closer to the one implied by the asset pricing model, or to any of those implied by some alternative models. The asset pricing model is supported by the test since it has significantly better out-of-sample fit on survey data than simpler models including the random walk. The traditional test based on forecasting ability is applied as well. The asset pricing model proves to have better forecast accuracy in case of some exchange rates and forecast horizons than the random walk.
Keywords: F31; F36; G13; 330; asset pricing exchange rate model; present value model of exchange rate; survey data; CAPM; Wechselkurs; Random Walk; Prognoseverfahren; Schätzung